Power Plays, Power Works - Fiske John (Verso, 1992)
The cultural wars which are raging across the United States today. Power and Cultural Theory, Power Plays, U.S. Cultures and European Theories, Controlling Bodies, Bodies of Language, Sporting Spectacles: The Body Visible, Elvis: A Body of Controversy, The Body of Violence, Representing and Knowing, Act Globally and Think Locally, Gunfight at the P.C. Corral, Local Knowledge, Things and Practices, White Power and Black Power, Blackened White, Power Works, Counter Power Works, Coda: The Slave Ship, Index.